1990
DOI: 10.1002/app.1990.070390508
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen permeability of teflon–PFA tubing

Abstract: SynopsisThe permeability coefficient for oxygen diffusing through a sample of Teflon-PFA tubing was determined experimentally. The source of the diffusing oxygen was ambient temperature air surrounding a coiled length of the PFA tubing. High pressure nitrogen was directed through the center of the PFA tubing. Oxygen permeating from the low pressure ambient air source, through the PFA tubing, and into the flowing high pressure nitrogen was observed in the effluent gases as they passed through a trace oxygen ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

1991
1991
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…Therefore, in this work we challenged ourselves to develop materials based on non-oxidisable fluorinated polymers and the luminescent molybdenum clusters. Importantly fluorinated polymers are well known to have good oxygen permeability and have been used for example, in oxygen sensing applications [16][17][18] and as an oxygen carrier in artificial blood [19].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in this work we challenged ourselves to develop materials based on non-oxidisable fluorinated polymers and the luminescent molybdenum clusters. Importantly fluorinated polymers are well known to have good oxygen permeability and have been used for example, in oxygen sensing applications [16][17][18] and as an oxygen carrier in artificial blood [19].…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned above, we expect that polar sites are formed due to the leakage of O 2 into the reactor 1315 along with the formation of free radicals due to crushing silica by the rocking action of the reactor. 16 Previous reports have shown that hot H 2 gas is capable of reducing oxidized carbon surfaces.…”
Section: Resultsmentioning
confidence: 93%
“…Here, the stainlesssteel tubing was replaced with highly hydrophobic perflouroalkoxy (PFA) tubing (5 ml, 2.5 m, 1.6 mm ID). Despite its oxygen permeability, 57 the material has already been used for successful synthesis of high order polymer nano-objects via PISA. 45,46 To obtain kinetic profiles of the continuous-flow ultrafast RAFT dispersion polymerisation experiments, transient kinetic studies were conducted for the chain extension of PDMAm 113 macro-CTA with 50, 100 and 200 equivalents of DAAm (Fig.…”
Section: Resultsmentioning
confidence: 99%